Unraveling Cyberlaw and Robots: A Quantitative Analysis - Aviva, Srivit; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article presents a quantitative analysis of the relationship between cyberlaw and robots using structured data from scholarly works. The research utilized data collected through documentation techniques, including numerical data and tables, sourced from Lens.org. The study aims to assist academics and researchers by providing a systematic and organized dataset for their work, facilitating communication, and serving as a reference for future research endeavors. The analysis reveals that cyberlaw, robots, business, and sociology are interconnected in the current technological landscape, potentially leading to future conflicts and societal challenges. The data highlights the importance of legal regulations in addressing the positive and negative aspects of robotics in society. Additionally, the article identifies the most active authors and top countries accessing Lens.org content on cyberlaw and robots, emphasizing the global significance of this field. Elsevier stands out as the top publisher, and IET Intelligent Transport Systems is recognized as a leading journal in this domain. In a world increasingly reliant on technology, this research underlines the importance of academic writing and the role of open access in advancing knowledge. Highlights: Quantitative data analysis explores the intricate relationship between cyberlaw and robots using structured data. The interconnectedness of cyberlaw, robots, business, and sociology presents potential future challenges and global implications. The study emphasizes the significance of legal regulations in addressing the impact of robots on society and underscores the role of open access in advancing knowledge. Keywords: cyberlaw, robot, data analysis, Lens.org, legal regulations